2002
DOI: 10.1111/j.1744-7429.2002.tb00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Species and Trophic Composition of Insect Communities in Puerto Rico1

Abstract: Insects are important participants in many ecosystem processes, but the effects of anthropogenic and natural disturbances on insect communities have been poorly studied. To describe how disturbances affect insect communities, we addressed two questions: Do insect communities return to a pre-hurricane composition? And how do insect communities change during succession? To answer these questions, we studied insect communities in a chronosequence of two abandoned pastures (5 yr and 32 yr) and a mature forest (>80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…In Florida, many common herbivores and seed predators disappeared for more than seven months afcer Hurricane Andrew (Pascarella 1998, Koptur et al 2002. Other studies have shown a diversity of responses by insects to hurricanes, with some groups increasing and others decreasing (Torres 1992;Schowalter 1994Schowalter , 1995Garrison & Willig 1996;Schowalter & Ganio 1999;Barberena-Arias & Aide 2002). Without data on specific herbivore species, it is difficult to determine if this was the major reason for lower levels of herbivory in our study.…”
Section: Discussionmentioning
confidence: 71%
“…In Florida, many common herbivores and seed predators disappeared for more than seven months afcer Hurricane Andrew (Pascarella 1998, Koptur et al 2002. Other studies have shown a diversity of responses by insects to hurricanes, with some groups increasing and others decreasing (Torres 1992;Schowalter 1994Schowalter , 1995Garrison & Willig 1996;Schowalter & Ganio 1999;Barberena-Arias & Aide 2002). Without data on specific herbivore species, it is difficult to determine if this was the major reason for lower levels of herbivory in our study.…”
Section: Discussionmentioning
confidence: 71%
“…We must bear in mind that at our site, plantations are presently embedded in a forest matrix. Although soils were profoundly disturbed by cattle ranching for several decades, there were remnant forest patches in the region that presumably served as recolonization sources and litter insect communities may recover rapidly after a perturbation (Barberena‐Arias & Aide 2002). In this case, the best chance to recover a fully functional tropical forest, with a species composition and structure resembling the original forest, is probably through natural regeneration (Murcia 1997), although preliminary work to restore soils may be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Barberena-Arias and Aide [90] and Osorio-Pérez et al [91] studied litter insect diversity and trophic composition during plant secondary succession in Puerto Rico. They found that arthropod species composition was significantly different between early and intermediate/late forests where early successional habitats had few unique species, and intermediate/late habitats had more species specific to woody habitats-suggesting the recovery of arthropod diversity during plant secondary succession is dependent not only on the increase of wood and concomitant resources but also on the recovery of plant diversity [92].…”
Section: Invertebrate Responses To Disturbance Gradientsmentioning
confidence: 99%